EXTH-09. HSP90 INHIBITION AS A NOVEL THERAPY FOR DIFFUSE INTRINSIC PONTINE GLIOMA (DIPG). (14th November 2022) - Sbergio, Stefanie-Grace; Sheth, Javal; Canty, Laura; Pajovic, Sanja; Vadivel, Arun Anguraj; Carette, Sheyenne; Siddaway, Robert; Hawkins, Cynthia
Abstract: Diffuse intrinsic pontine glioma (DIPG) is an aggressive pediatric brain tumor. The mean age of onset is 7-9 years with a median survival of 9 months following diagnosis. Histone 3 (H3) mutations (H3K27M) have been identified in approximately 80% of patients, representing an intriguing target, but how to do this is unclear. To address this, we performed a synthetic lethality drug screen of over 2400 compounds on isogenic cells expressing H3K27M and empty vector. 37 drugs were synthetically lethal with H3K27M, including HSP90 inhibitors. In cancer, HSP90 has a higher isoelectric point which can be targeted specifically by PU-H71. Using PU-H71, HSP90 complexed with oncogenic clients can be inhibited to reduce tumor cell viability. We tested PU-H71 on primary patient derived DIPG lines demonstrating caspase-3/7 mediated cell death within 24 hours (n=3) and an IC50 of 100-200 nM (n=5) at 72 hours. HSP90 is a molecular chaperone that supports protein activation and localization; thus, its inhibition may allow simultaneous targeting of multiple oncogenic pathways. To determine which pathways are targeted in DIPG we used PU-H71-conjugated beads to pull-down HSP90 complexed with client proteins. LC-MS/MS characterization of the HSP90 interactome from three DIPG cell lines (SU-DIPG XVII, SU-DIPGXXV, SU-DIPG 50) identified 339 overlapping proteins including MAPK3, SMS, SRM, CTSP1, OAT, GMPS, and PYG. Pathway enrichment analysis highlighted roles in cell cycle regulation and metabolic processes. Treating DIPG with PU-H71 successfully reduced tumor cell viability but PU-H71 has poor brain penetration. To overcome this, a molecular isoform of PU-H71 has been developed, PU-HZ151, which will be used to test the in vivo efficacy of HSP90 inhibition for DIPG.